DISASTER AS CLICKBAIT: SENSATIONALISM, EMOTIONAL AMPLIFICATION AND DIGITAL MEDIATION IN TIKTOK COVERAGE OF THE ACEH TAMIANG FLOOD - Kevin Rasyid Sabili Nasution; Dinda Rezeki Amaliyah; Eva F.M; Rahmanita Ginting (Journal Analytica Islamica, 2026)
This study aims to analyze how the Aceh Tamiang flood is constructed as a social reality on TikTok through practices of sensationalism, emotional amplification, and algorithm-based digital mediation. The study departs from the understanding that social media no longer functions merely as a channel for information dissemination, but rather as a central arena for the formation of meaning, collective emotion, and public attention toward disaster events. Within this context, flooding is not only presented as a natural phenomenon, but as a visual and emotional narrative that is produced, selected, and highlighted in accordance with the logic of digital platforms.The research adopts a qualitative approach using interpretive content analysis of TikTok content related to news coverage of the Aceh Tamiang flood. Data were collected through digital observation, content documentation, and monitoring of public conversations using Brand24 to identify emotional patterns, keywords, and the dynamics of audience attention. Data analysis was conducted using the Miles, Huberman, and Saldaña model, encompassing data condensation, data display, and conclusion drawing, and was strengthened through data source triangulation. The findings indicate that TikTok coverage of the Aceh Tamiang flood is dominated by dramatic visual representations and emotional narratives emphasizing suffering, solidarity, and humanitarian action. Emotions of sadness, admiration, and joy emerge as the primary affective spectrum shaping audience resonance and driving high levels of engagement. Audience reception reveals diverse positions of meaning-making, ranging from dominant acceptance of humanitarian narratives, to negotiated readings through structural critique, and to oppositional interpretations that politicize the disaster. These findings underscore that within the logic of the Network Society, flooding is transformed into clickbait operating as a commodity of attention, in which emotion, algorithms, and audience participation are deeply intertwined in shaping the reality of disaster in the digital public sphere.